The Essence and General Characteristics of Methods for Assessing the Competitiveness of an Enterprise - Vinnychenko Olena V. (Bìznes Inform, 2024)
The article examines the theoretical aspects of the essence of the concept of «enterprise competitiveness». A company’s competitiveness depends on its internal state and external position. It determines a company’s ability to successfully compete and stand up to its main competitors in a given period of time, rather than being a permanent characteristic of a company. The problematics of competitiveness is the subject of research by many domestic and foreign scientists. The analysis carried out in the publication indicates a fairly wide composition of the concept of «enterprise competitiveness», which indicates the lack of a unified approach to the definition of this concept. For the theoretical generalization of the interpretations of the term «enterprise competitiveness» by various authors, a morphological decomposition was carried out in order to determine the most typical approaches to understanding this concept. A comparative analysis of the main methods for assessing competitiveness has been carried out and the advantages and disadvantages of each of them have been allocated. The obtained results allow us to conclude that the competitiveness of enterprise is an integral indicator that characterizes the advantages of the enterprise and the ability to develop in accordance with the strategy, having the ability to effectively use competitive advantages and increase its presence in the market, under conditions of conducting effective financial and economic activities while optimizing costs and improving product quality.